Classification of the Socio-Psychological Aspects of Protecting Soft Targets: a Case Study for Evacuation of the Railway Terminals - Alena Šplíchalová; Tomáš Karásek; Tomáš Apeltauer (Communications - Scientific letters of the University of Zilina, 2021)
Current crisis management approaches to protect soft targets make assumptions about average visitors/listeners/viewers or passengers. They do not give much consideration to impacts of diversity of potentially evacuated persons with regard to socio-psychological parameters/factors that may lead to practical problems and complications during the evacuation itself. At the same time, the soft target operators have various means of machine vision tools at their disposal, but do not use these records for more thorough analysis of evacuation planning needs. Based on this observation, the article identifies and analyzes the socio-psychological aspects that may significantly affect behavior and decisions of persons during the evacuation and thus total evacuation time.